Escovopsis trichodermoides sp nov., isolated from a nest of the lower attine ant Mycocepurus goeldii - Masiulionis, Virginia Elena [UNESP]; Cabello, Marta N.; Seifert, Keith A.; Rodrigues, André [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Springer, 2015)
Currently, five species are formally described in Escovopsis, a specialized mycoparasitic genus of fungus gardens of attine ants (Hymenoptera: Formicidae: tribe Attini). Four species were isolated from leaf-cutting ants in Brazil, including Escovopsis moelleri and Escovopsis microspora from nests of Acromyrmex subterraneus molestans, Escovopsis weberi from a nest of Atta sp. and Escovopsis lentecrescens from a nest of Acromyrmex subterraneus subterraneus. The fifth species, Escovopsis aspergilloides was isolated from a nest of the higher attine ant Trachymyrmex ruthae from Trinidad. Here, we describe a new species, Escovopsis trichodermoides isolated from a fungus garden of the lower attine ant Mycocepurus goeldii, which differs from the five other species by highly branched, trichoderma-like conidiophores lacking swollen vesicles, with reduced conidiogenous cells and distinctive conidia morphology. Phylogenetic analyses based on partial tef1 gene sequences support the distinctiveness of this species. A portion of the internal transcribed spacers of the nuclear rDNA was sequenced to serve as a DNA barcode. Future molecular and morphological studies in this group of fungi will certainly unravel the taxonomic diversity of Escovopsis associated with fungus-growing ants.
Keywords: Attini; Fungus-growing ant; Hypocreales; Mycoparasitism